STUDI DAMPAK EMISI SUKUK DAN RASIO KECUKUPAN MODAL TERHADAP PROFITABILITAS ASET PADA BANK PANIN SYARIAH, TBK - Yulia Safitri Harahap; Budi Gautama Siregar; Aswadi Lubis (Jurnal Mahasiswa Akuntansi Samudra, 2025)
This study aims to examine the effect of sukuk issuance and the Capital Adequacy Ratio (CAR) on Return on Assets (ROA) at PT. Bank Panin Syariah, Tbk. The research employs a quantitative approach using multiple linear regression analysis, based on quarterly financial reports from the period 2012 to 2020. The partial test results indicate that sukuk issuance does not have a significant effect on ROA, while CAR has a positive and significant effect. Simultaneously, both variables are found to have a significant influence on ROA. These findings highlight that capital adequacy plays a crucial role in enhancing the bank’s profitability, whereas the effectiveness of sukuk fund utilization still needs improvement. This study implies that strengthening capital structure and improving the efficiency of sharia-based fund management are strategic factors in supporting the sustainable financial performance of Islamic banks. However, this study has several limitations, including limitations in the number of samples that only focus on one Islamic bank, as well as a limited research period from 2012 to 2020. In addition, the variables used in the analysis are still limited to the issuance of sukuk and CAR, so they do not include other factors that can also affect the bank's profitability. Therefore, further research is expected to involve more institutions and variables to obtain more comprehensive results